eran komunikasi efektif dalam meningkatkan layanan ?perpustakaan - Diah Qonita Rahma; Fitrimawati‎ Fitrimawati‎; Eny Supriati‎; Ayu Wulansari; Antis Ramayanti (IJAL (Indonesian Journal of Academic Librarianship), 2023)
Effective communication is the backbone of all human interactions, especially in service contexts like libraries. This article explores how good and effective communication improves library services, focusing on a case study at the Muhammadiyah University Ponorogo Library. Through qualitative descriptive research methods that include observation, interviews, and documentation, the results show the crucial role of effective communication in improving service standards at the Muhammadiyah University Ponorogo Library, considering theories, especially Diniaty's approach, namely the importance of communication in changing user attitudes and behavior. Good communication between librarians and users, especially in rule enforcement, significantly improves compliance with regulations. Apart from that, the dedication of librarians to providing optimal service solutions, in line with the Wijayanti concept, is further strengthened by effective communication in managing services in the library. Recommendations for improving service quality include expanding efforts to strengthen effective communication among all library stakeholders through training and developing communication skills for staff, which is expected to create a better communication environment and, in turn, improve user experience in using library services.